Penggunaan Eceng Gondok Sebagai Filler untuk Meningkatkan Kuat Mekanik Batako Ringan Berbahan Dasar Limbah Emas - Iin Sugianto; Dwi Sabda Budi Prasetya; Sukainil Ahzan (Universitas Pendidikan Mandalika, 2018)
[Title: The use of water hyacinth as a filler to improve the strength of lightweight brick making based on gold waste]. Research objectives is to testing the compression of lightweight brick. This research was conducted through three stages: Creating lightweight bricks (from waste mining of gold and water hyacinth) horizontally, orthogonally, and randomly. Characterization of the sample as follows: density, and compressive strength. The results show that the best compression analysis at low densities of light bricks horizontally, orthogonally and randomly in compositions: 70% GMW + 30% WH = 0.54MPa, 70% GMW + 30% WH = 1.18MPa, and 85% GMW + 15% WH = 0.73 MPa. Whereas, the density test horizontally, orthogonally, and randomly in composition variations of water hyacinth as follows: 70% GMW + 30% WH = 1.41gr/cm3, 3.40% GMW + 60% WH = 1.89gr/cm3, 85% GMW + 15 WH = 1.20 gr/cm3. It can be concluded that the filler composition is directly proportional to the compressive strength. In addition, the density is inversely proportional to the mass of the lightweight brick.